Opportunities and challenges in using WPAN and WLAN technologies in medical environments. - Soomro, Amjad (IEEE Communications magazine)
The present view of medical environments, where isolated networks are used for IT and medical applications, is changing toward an integrated heterogeneous network scenario that can support a wide range of applications. WPAN and WLAN technologies play a fundamental role in enabling such integrated environment that is expected to support both medical and nonmedical applications. The ultimate goal is to exploit WPAN and WLAN technologies, as well as other wireless networks, such as 3G cellular systems and satellite networks, to support highly efficient medical care delivery, anytime and anywhere. However, the life-critical nature of some medical applications imposes additional challenges that have not been considered in nonmedical scenarios. This article discusses some future scenarios where WLAN and WPAN technologies can be used to provide an integrated and ubiquitous network in medical environments, and identifies the main issues to be addressed in order to meet the QoS requirements of different medical applications when operating in integrated environment.